Community empowerment on how to make fish nuggets and covid-19 vaccination service in Buol Regency - Alfi Sahri R Baruadi; Fernandy M Djailani; La Nane (Fisheries and Society, 2022)
Buol regency is a regency in the central of Sulawesi, Indonesia that has a lot of fisheries resources commodity. One of them is milk fish. Economic and social issues are still the main issues in Buol Regency. Community empowerment by training activities are needed to make fish nuggets to improve the economy and assistance in vaccination of the Covid-19 program as part of the government program to pass the outbreak of virus in 2022. This activity was carried out for 45 days in Kantanan Village and Negeri Lama Village. There are a total of 20 students as companions in the two villages. The method used in this service is the training method, through mentoring and practice. Participants could be easily understand and practice it well. The results obtained from this activity are nuggets of milk fish and the implementation of the vaccination program at the both village. The achievement of the vaccination program in the two villages is 85%. In conclusion, this community service program has been running well and achieving its targets to create and help community in Buol Regency.